2014
DOI: 10.1186/1471-2261-14-163
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the pooled cohort risk score in an Asian population – a retrospective cohort study

Abstract: BackgroundThe Pooled Cohort Risk Equation was introduced by the American College of Cardiology (ACC) and American Heart Association (AHA) 2013 in their Blood Cholesterol Guideline to estimate the 10-year atherosclerotic cardiovascular disease (ASCVD) risk. However, absence of Asian ethnicity in the contemporary cohorts and limited studies to examine the use of the risk score limit the applicability of the equation in an Asian population. This study examines the validity of the pooled cohort risk score in a pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 25 publications
5
45
1
3
Order By: Relevance
“…During the writing process of this study, there is no reference of the ASCVD risk information for Indonesian subjects. According to a reference, the ASCVD risk method appeared to overestimate absolute ASCVD risk as the observed events were less than predicted [8]. A similar finding in an external calibration on ASCVD risk, the result showed that the method in 15 cohort studies, reanalyzed studies, or external calibration overestimated the ASCVD risk in almost all studies.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…During the writing process of this study, there is no reference of the ASCVD risk information for Indonesian subjects. According to a reference, the ASCVD risk method appeared to overestimate absolute ASCVD risk as the observed events were less than predicted [8]. A similar finding in an external calibration on ASCVD risk, the result showed that the method in 15 cohort studies, reanalyzed studies, or external calibration overestimated the ASCVD risk in almost all studies.…”
Section: Discussionsupporting
confidence: 68%
“…The ASCVD risk showed moderate discrimination and good calibration in an Asian population. The moderate discrimination due to the high prevalence of ASCVD risk factors was improved with clustering of higher risk patients, whereas fewer patients were needed among the patients with lower risk [8]. Therefore in a general population of subjects with a wider range of ASCVD risk, the risk prediction using PCE method may give a better discrimination [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many articles reported a low prevalence of statin use at study baseline; in those situations, it may have been assumed that treatment would not have greatly influenced the predicted probabilities. However, treatment use can greatly change over time, as shown by one study validating the AHA/ACC Pooled Cohort Equations [16], which reported increases in antihypertensive medication use and statin use from 59.9 to 82.4% and 9.7 to 63.7%, respectively, over a 10-year follow-up period (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007) [17]. Second, while only nine articles reported that data on treatments were not available in their studies, it might be that more studies were unable to obtain such data, especially follow-up information, as this may be more costly or difficult to collect.…”
Section: Discussionmentioning
confidence: 99%
“…We considered three risk categories, <10% (low), 10–20% (intermediate) and >20% (high). We did not consider the 2013 American College of Cardiology / American Heart Association (ACC/AHA) Pooled Cohort Equation17 because it was developed including stroke and because it has been shown to overestimate cardiovascular disease (CVD) risk, particularly in Asian populations 18…”
Section: Methodsmentioning
confidence: 99%